Clinically Isolated Syndrome Suggestive of Multiple Sclerosis: Voxelwise Regional Investigation of White and Gray Matter - Raz, Eytan; Cercignani, Mara; Sbardella, Emilia; Totaro, Porzia; Pozzilli, Carlo; Bozzali, Marco; Pantano, Patrizia (Radiology, 2010)
To quantify white matter (WM) and gray matter (GM) damage in patients who presented with clinically isolated syndrome (CIS), which is suggestive of multiple sclerosis (MS), by combining volume-based morphometry (VBM) and tract-based spatial statistics (TBSS). This prospective HIPAA-compliant study was approved by the institutional review board. Written informed consent was obtained from all participants. In this study, 34 consecutive patients (21 women, 13 men; mean age, 31.7 years +/- 7.7 [standard deviation]) who presented with CIS were recruited. The magnetic resonance (MR) examination included dual-echo fast spin-echo, three-dimensional T1, and diffusion-tensor imaging. Sixteen matched healthy volunteers served as control subjects. T2 lesion volumes were assessed with a semiautomatic technique. VBM and TBSS were used for the GM and WM analyses, respectively, to compare regional GM volumes and fractional anisotropy (FA) values in the two groups. TBSS analysis revealed a pattern of diffuse FA reductions in patients with CIS at the cluster level (P < .05). Regions of decreased FA involved most of the WM pathways, including the corticospinal tracts, corpus callosum, and superior and inferior longitudinal fasciculi. There were no significant differences between the two groups in terms of global GM, WM, or cerebrospinal fluid volume or in terms of regional GM volume. Diffuse WM damage not accompanied by any change in GM or WM volume is observed in patients with CIS. This suggests that WM involvement plays a relevant role in the early phases of MS. Subsequently detected GM damage may be secondary to WM alterations.